Using social network analysis to investigate interorganizational relationships and capacity building within a sport for development coalition - Hambrick, Marion E.; Svensson, Per G.; Kang, Seungmin (Sport management review, 2019)
•A sport for development coalition involving 27 agencies and 5 networks was examined.•Social network analysis was used to study the coalition networks and relationships.•The networks provided access to resources such as information and infrastructure.•Network advantages included better service delivery to community and clients. Sport for development (SFD) agencies often face issues with resource dependency, where they encounter resource deficiencies and rely upon other organizations to build capacity and attain their organizational goals and objectives. The purpose of this study was to investigate what resource networks existed among agencies within a city-wide SFD coalition and the advantages and disadvantages of their participation. The authors examined an SFD coalition involving 27 agencies and their five resource networks: information, finance, human resources, infrastructure, and strategic planning. Results indicate the SFD agencies developed relationships across the five networks. A subgroup of well-connected agencies shared numerous relationships spanning multiple networks, and they assumed central positions with greater access to resources and more capacity in these networks. Coalition advantages, such as better service delivery to clients, outweighed disadvantages, such as limited time. The findings indicated the potential for SFD agencies to cultivate relationships, gain access to resources, and build capacity within these interorganizational networks.